Realization of logical meaning in Christian and Moslem Debate on Soco Films - Silitonga, Harpen H.P (JETAL: Journal of English Teaching & Applied Linguistic, 2024)
This study is a critical discourse analysis study of metafunctions as part of the ideational function. And this research focus on the interpendency taxis system, namely parataxis and hypotaxis and relationship from logical semantics to expansion and projection in the analysis of Christian and Moslem Debate on SOCO films. By looking at the main focus and the overall analysis of this research, then study answered the following questions; what types of taxis are used in Christian and Moslem Debate on SOCO films and how the type of taxis are used in Christian and Moslem Debate on SOCO films. The Data were analized by descriptive qualitative analysis. The hypotaxis construction is more frequently occured than parataxis construction. It appears 136 times or 63.55%, meanwhile parataxis construction only appears 78 times or 36.45%.